Cadre Role and Performance in Preventing Stunting in Dolo, Central Sulawesi - Revi Ekasetya Pratiwi; Eka Diah Kartiningrum; Rifaatul Laila Mahmudah (Journal of Public Health and Pharmacy, 2025)
Introduction: Indonesia has the highest rate of stunting among toddlers in Southeast Asia, with a prevalence of 31.0%. A 2022 survey on nutritional status conducted across 33 Indonesian provinces ranked Central Sulawesi 6th highest for stunting, at 28.2%. Within 13 regencies/cities in Central Sulawesi province, Sigi regency had the highest stunting rate, reaching 36.8% among toddlers. Data from the Dolo Community Health Center showed a local prevalence of stunting at 14.7% in 2022. This figure remains high compared to the government's annual standard of 3.8%. The Community Health Worker program in 12 countries prevents stunting by providing nutrition education, monitoring child growth, promoting exclusive breastfeeding, and distributing additional foods and supplements. As the main pillars for improving public health, cadres are crucial in preventing stunting. Therefore, this study aimed to analyze the role and performance of cadres in preventing stunting in the Dolo, Central Sulawesi. Methods: A qualitative case study design was adopted from March to July 2024 in Dolo, Central Sulawesi. Furthermore, 15 informants were selected by purposive sampling, including three key informants, seven primary informants, and five additional informants. Data collection involved participant observation, in-depth interviews, documentation, and focus group discussions. Analysis followed three steps: reduction, data display, and conclusion drawing/verification. Ethical approval was received from Majapahit Health Sciences College, Number: 04 /EC-SM/2024. Results: The results showed that stunting cadres in the Dolo, Central Sulawesi, effectively fulfilled their role and responsibilities across various stages of intervention. However, several challenges were identified, including limitations in conducting home visits. Conclusion: Cadre performance in Dolo requires a comprehensive approach, namely setting a minimum standard for each cadre's frequency of home visits. Stakeholders provide refresher training every six months and conduct periodic evaluations of cadre effectiveness.